PENGARUH FINANCIAL LITERACY, JENJANG PENDIDIKAN DAN PENGETAHUAN AKUNTANSI TERHADAO PENGGUNAAN INFORMASI AKUNTANSI PADA UMKM DI KOTA BATAM - Maharani Wibawa, Zahra; Christian L Tobing, Vargo (LPPM Universitas Putera Batam, 2024)
This research was conducted with the aim of testing and evaluating the influence of Financial Literacy, Educational Level and Accounting Knowledge on the Use of Accounting Information among MSMEs in Batam City. The population in this research is MSME actors in Batu Aji District who are registered at the Batam City Cooperative and MSME Office, namely 164 MSME actors. For the research sample in this study, random sampling techniques were used using the Slovin formula. The results of the Slovin formula calculation, obtained a figure of 116.3 rounded up to 116 respondents. The data used in this research is primary data resulting from distributing questionnaires to MSME players. This research uses quantitative methods, analyzing using descriptive analysis tests, instrument tests, classical assumption tests, multiple linear analysis and hypothesis testing using the IBM SPSS version 25 software program. Based on the results of hypothesis testing (t-test) it is stated that financial literacy, level of education and accounting knowledge partially has a significant effect on the use of accounting information. The results of the simultaneous test (f-test) state that financial literacy, education level and accounting knowledge simultaneously have a significant effect on the use of accounting information. Keywords: Financial Literacy; Education Level; Accounting Knowledge; Use of Accounting Information